TALENT MANAGEMENT IN HEALTHCARE SECTOR: INSIGHT INTO THE CURRENT IMPLEMENTATION IN SLOVAK ORGANIZATIONS - Ali Taha, Viktória; Gajdzik, Tomáš; Abu Zaid, Júlia (European Scientific Journal, ESJ, 2015)
In today’s global highly competitive marketplace, the success of the organizations is largely determined by implementation of talent management encompassing wide range of processes designed to identify, attract, develop, retain and deploy talented people with required skills. The article seeks to provide analytical insight into the talent management processes in Slovak healthcare sector. The aim of this study is on the basis of analysis of primary data collected through the questionnaire survey to examine and assess selected practices/processes of talent management in Slovak health/healthcare organizations. Using methods of inductive statistics (nonparametric Kruskal-Wallis test) we examined the existence of statistically significant differences between organizations of different size.